2017
DOI: 10.1186/s13005-017-0136-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the degree and direction of nasal septum deviation and nasal bone morphology

Abstract: BackgroundNasal septal deviation may affect nasal bone growth and facial morphology. Knowledge of nasal morphologic parameters may plays an important role in planning successful rhinoplasty and septoplasty operation. The aim of our study was to evaluate the relationship between the direction and degree of nasal septal deviation with nasal bone morphology, along with factors such as age and gender.MethodsMaxillofacial computed tomography (CT) of 250 patients with nasal septal deviation was analyzed retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 19 publications
4
41
2
2
Order By: Relevance
“…Nasal septal deviation, seen in about 80% of the population, is defined as an asymmetry of the nasal septum, and it may limit air flow and impair the growth of the paranasal sinus. As a consequence, mucosal ciliary activity decreases and bacterial invasion develops [6][7][8]. Additionally, previous studies stated that concha bullosa (pneumatized middle turbinate) adversely affects the paranasal sinus ventilation and mucociliary clearance in the middle meatus region [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nasal septal deviation, seen in about 80% of the population, is defined as an asymmetry of the nasal septum, and it may limit air flow and impair the growth of the paranasal sinus. As a consequence, mucosal ciliary activity decreases and bacterial invasion develops [6][7][8]. Additionally, previous studies stated that concha bullosa (pneumatized middle turbinate) adversely affects the paranasal sinus ventilation and mucociliary clearance in the middle meatus region [9].…”
Section: Introductionmentioning
confidence: 99%
“…Concha Bullosa (CB) also known as middle turbinate pneumatization or aerated turbinate, is a common anatomic variant in the nasal cavity and may occur unilaterally or bilaterally 12 . The correlation between the presence of CB and contralateral NSD has been reported in different studies 12, 13 . However, the claim that presence of NSD and pneumatization of the conchae are potential contributors to the development of sinus disease is still a matter of debate 14 .…”
Section: Introductionmentioning
confidence: 75%
“…It is well known that NSD and CB are common anatomical variations of the nasal cavity and have been described in different studies 10, 22 . The proper alignment of the nasal septum allows the operation of the two sides of the nose which in turn provides both conditioning of the air and respiratory defense 13 .NSD may therefore interfere with nasal physiology as it frequently causes narrowing of the middle nasal meatus which in turn causes nasal obstruction and secondary nasal and sinus infections. These infections are most frequently observed in the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the angle of nasal septum deviation was 7.56±2.60 in men and 6.86±2.57 in women. In another study 10 , examiners found the angle of the nasal septum deviation 13.88˚ (4.9-31.2) in males and 14.18˚ (5.1-34.1) in females in which only individuals with nasal septum deviation were examined. As in this study, correlation between age, gender and deviation couldn't be found.…”
Section: Discussionmentioning
confidence: 99%